Does engagement help to reduce insomnia when workers are emotionally exhausted? - Fernández-Salinero, Samuel; Topa, Gabriela; Fernández Muñoz, Juan José (Sleep and biological rhythms, 2023)
Insomnia is one of the most common problems, affecting more than 35% of the world’s population. To achieve a better understanding of this problem the focus of this research is to understand how emotional exhaustion at work may lead to insomnia. To help to combat it, we tested a mediation model including engagement factors. The sample was composed of 823 participants. 38.3% (315 subjects) were male and 61.7% (508 subjects) were female. Mean age was 42.65 years old (9.05 = SD). Main results showed that emotional exhaustion is directly and statistically significant related to insomnia. However, different engagement factors showed different weights in buffering this relationship. Emotional exhaustion showed a statistically significant impact on insomnia. Vigor and absorption helped to buffer the impact of emotional exhaustion over insomnia. Our study has some limitations. First, the sample was acquired by not aleatory processes. Another limitation is that our sample was composed of individuals with decision-making capacity. Lastly, our research is a transversal study. Future research should take these limitations into account and conduct longitudinal research with aleatory sampling procedures.